Perlindungan Hukum Dalam Manajemen Keamanan Dan Kesejahteraan Kurir - Saifudin .; Dudik Djaja Sidart; Moh. Taufik (JOURNAL OF SHARIA ECONOMICS, 2022)
Couriers are at the forefront of the logistics and e-commerce industry, which continues to grow rapidly. As a job that faces various physical challenges and risks, legal protection for the safety and welfare of couriers is an increasingly important issue. Although many logistics companies provide certain guarantees, issues related to work safety, fair wages, and courier health and welfare benefits are still a frequent concern. This research aims to examine the legal protection that exists in the management of security and welfare of couriers in Indonesia, as well as the challenges and solutions that can be implemented. This research uses a qualitative approach with in-depth interview methods and literature studies to explore the views of legal experts, industry practitioners and couriers themselves. The research results show that although there are regulations governing worker protection, inconsistent implementation and unclear worker status in many logistics companies mean that couriers often do not receive proper protection. This article provides recommendations for improving existing regulations and practices to ensure job security and welfare for couriers in Indonesia.